Некоторые особенности термостабилизации композиций на основе поливинилбутираля - П. С. Восканян (ՀՀ ԳԱԱ հրատ.)
Изучена температурная зависимость растворимости фосфорсодержащих соединений в пластифицированном поливинилбутирале. На основании полученных результатов определено, что наиболее приемлемым фосфорсодержащим соединением является стафор-II, растворимость которого в поливинилбутирале выше, чем концентрация, необходимая для торможения окисления. Установлено, что тип пластификатора (дигексиладипинат, дибутилсебацинат) незначительно влияет на растворимость стабилизаторов в поливинилбутирале. Выявлено, что стеарат кальция уменьшает скорость поглощения кислорода на глубоких стадиях реакции окисления полимера. Ուսունասիրված է ֆոսֆոր պարունակող միացությունների լուծելիության ջերմային կախվածությունը պլաստիկացված պոլիվինիլբուտիրալում: Հաստատված է, որ լուծելիությունը ֆոսֆոր պարունակող կայունարարներում թույլ է կախված պլաստիկարար նյութի տիպից (դիհեքսիլադիպինատ կամ դիբուտիլսեբացինատ), բայց ուժեղ է կախված հակաօքսիդիչից: Առավել բարձր լուծելիություն ցածր ջերմաստիճանների դեպքում դիտվում է ստաֆոր-II-ի մոտ (6% 20 0C-ի դեպքում): The purpose of the present work is studying of temperature dependence of solubility of phosphorus-containing connections in plasticized polyvinylbutyral, with selection of optimum compatible additives in polyvinylbutyral since while working-out of optically transparent compositions it should be known the limiting concentration of antioxidants which do not lead to turbidity of a polymer. The temperature dependence of phosphorus-containing connections solubility in plasticized polyvinylbutyral is studied. It is determined that the solubility of phosphorus-containing stabilizers poorly depends on a type of plasticizer (di-n-hexyl-adipate or dibutylsebacate), but strongly depends on an antioxidant. The highest solubility at low temperatures is observed for staphor - II (6% at 20°C).
Keywords: Chemistry; Polymeric Chemistry